ANALISIS PERBEDAAN KOMPETENSI SDM DAN PRODUKTIVITAS USAHATANI HOERTIKULTURA ANTARA DESA SUMBERJO DAN SIDEREJO DI KECAMATAN WONOMULYO, KABUPATEN POLEWALI MANDAR - Andayani, Nining Diyah; Albar, Albar (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the differences in human resource (HR) competence and horticultural farm productivity between Sumberjo and Sidorejo Villages in Wonomulyo Subdistrict, Polewali Mandar Regency. HR competence encompasses aspects of knowledge, skills, experience, and attitudes in managing farming activities, which play a crucial role in enhancing the success of horticultural enterprises. The research employed a comparative quantitative approach with a sample of 60 respondents (30 farmers from each village) selected using purposive sampling. Data were collected through a Likert-scale questionnaire to measure HR competence, while productivity was calculated based on yield per hectare. The data were then analyzed using the Independent Sample T-Test at a 5% significance level. The results indicate significant differences between the two villages, where the average HR competence of farmers in Sidorejo Village (4.1 ± 0.4) was higher than that in Sumberjo Village (3.4 ± 0.5), with a p-value of 0.012. Similarly, farm productivity in Sidorejo (2.4 tons/ha ± 0.2) was higher compared to Sumberjo (1.8 tons/ha ± 0.3), with a p-value of 0.008. These findings confirm that higher HR competence has a positive impact on improving horticultural productivity.